Case Report on Nursing Management of Japanese Encephalitis with Convulsion (Journal of Pharmaceutical Negative Results, 2022)
Background: Japanese encephalitis (JE) is an important viral disease-causing fatal condition in children. Vaccination against JE is a significant preventive measure as the specific drugs are not available for treatment. It shows symptoms including Fever, altered sensorium, and Muscle. Patient presentation: We are presenting a 2-year-old male child who visited the pediatric outpatient unit with the symptoms of muscle rigidity, fever, and seizure, he was admitted to pediatric ward no.-17. He was a known case of Japanese Encephalitis. He was diagnosed to have seizures at the age of 1 year when he was admitted to the hospital due to fever. Till then, he was admitted to a private hospital from time to time because of a critical condition in PICU and was on higher multi anti-epileptics. There are not any abnormalities found in the head-to-toe examination, the child is thin and looks dull and also his muscle looks stiff and neck movements are very slow. He is a weak child. The patient’s physical and clinical examination was taken. He was treated with high multi-epileptics and physiotherapy is continued. After treatment, the patient’s condition improves. Symptoms such as fever, altered sensorium, and convulsion are minimized and muscle stiffness is improved. Conclusion: It can be transmitted to humans by mosquitoes belonging to the species Culex (mainly Culex tritaeniorhynchus), which breed mostly found in rice paddles. A mosquito carrying Japanese Encephalitis can transmit it by feeding on pigs and wild birds carrying the disease. It cannot be transmitted from person to person. As a result of the dramatic increase in vector populations during rainy seasons, diseases are highly transmitted. There is no cure for the disease, but there are vaccines that can prevent the spread of the disease. By treating the infection, the patient can protect themselves from further damage and will be relieved of severe clinical signs.